Fabrication of Au@CdS/RGO/TiO2 heterostructure for photoelectrochemical hydrogen production. (11th January 2016) - Li, Chunfa; Fan, Weiqiang; Lu, Huachang; Ge, Yilin; Bai, Hongye; Shi, Weidong
Abstract : Schematic energy band illustration of a novel Au@CdS/RGO/TiO2 heterostructure as a photoelectrode for PEC hydrogen generation via water splitting. Abstract : This study reports a novel Au@CdS/RGO/TiO2 heterostructure as a photoelectrode for photoelectrochemical (PEC) hydrogen generation via water splitting. The unique heterostructures of the Au@CdS/RGO/TiO2 photoelectrode were confirmed by scanning electron microscopy (SEM), transmission electron microscopy (TEM), Raman spectroscopy and X-ray photoelectron spectroscopy (XPS). Au@CdS nanoparticles with a core–shell structure were introduced into the TiO2 photoelectrode for the first time, and the Au@CdS nanoparticles could endow the TiO2 photoelectrode with both visible light response ability and the plasmonic property. Moreover, the RGO thin film sandwiched between TiO2 nanorod and Au@CdS core–shell nanoparticles played an important role in the fast transport of photogenerated charges, due to its excellent electrical conductivity. Clear enhancements of photocurrent and monochromatic incident photon-to-photocurrent efficiency were observed, resulting from the synergistic effect between Au@CdS core–shell nanoparticles and the RGO thin film. More importantly, Au@CdS/RGO/TiO2 photoelectrode achieved a considerable hydrogen evolution rate (4.821 mmol h −1 m −2 ) under full spectrum illumination (47 mW cm −2 ).